Stability Analysis for a Fractional HIV Infection Model with Nonlinear Incidence - Linli Zhang; Gang Huang; Anping Liu; Ruili Fan (Discrete Dynamics in Nature and Society)
We introduce the fractional-order derivatives into an HIV infection model with nonlinear incidence and show that the established model in this paper possesses nonnegative solution, as desired in any population dynamics. We also deal with the stability of the infection-free equilibrium, the immune-absence equilibrium, and the immune-presence equilibrium. Numerical simulations are carried out to illustrate the results.